Paralytic Ileus Secondary to Methamphetamine Abuse: A Rare Case - Mark Aidan McKelvie; Yuksel Gercek (Case Reports in Surgery)
Methamphetamine hydrochloride, colloquially referred to as “crystal meth,” is a potent psychoactive amphetamine derivate. Methamphetamine produces stimulant effects in the user including increased energy and alertness as well as inducing intense euphoric symptoms and suppressing appetite through its dopaminergic, serotonergic, and adrenergic actions. Use of methamphetamine can adversely affect cardiovascular, neurological, and gastrointestinal physiology leading to significant morbidity. We present a rare case of paralytic ileus secondary to methamphetamine abuse which has only once before been described in the literature.